The brain excitatory and inhibitory amino acids content in rats with lithium-pilocarpine-evoked seizures and after the preliminary administration of levetiracetam and novel racetam derivative GIZH-290 - I. G. Kovalev; R. O. Bokov; V. S. Kudrin; T. A. Voronina; G. I. Kovalev (LLC "Publisher OKI", 2017)
The effects of a new racetam derivative with anticonvulsant activity GIZh-290 (2-oxo-4-phenylpyrrolidin-1-yl) acetic acid and levetiracetam for the content of neuroactive amino acids aspartate, glutamate, taurine, glycine and GABA in homogenates of the hippocampus and prefrontal cortex (PFC) of rat brain using the HPLC method with fluorescent detection were studied. In the hippocampi of intact rats HIZh-290 (5 mg/kg, ip) increased the levels of glutamate, glycine and GABA by 22, 42 and 28 %, and levetiracetam (600 mg/kg), on the contrary, reduced them by 18, 26 and 26 %. At the maximum of lithium-pilocarpine seizures, a decrease in the content of aspartate (-19 %) and an increase in glycine in the PFC (+24 %) were detected. Preliminary administration of GIZh-290 and levetiracetam did not affect these parameters, but caused an increase in taurine concentrations in the PFC homogenates. Thus, the indicators studied are not markers of anticonvulsant action of levetiracetam and GIZH-290, but indicate differences in the mechanisms of the drugs anticonvulsant effect formation.